Satellite imagery and heritage damage in Egypt: a response to ‘Satellite evidence of archaeological site looting in Egypt: 2002–2013’ (Parcak et al. 2016) - Fradley, M; Sheldrick, N (Cambridge University Press, 2017)
In a recent article, Parcak et al. (2016) presented the results of a study in which they used satellite imagery to evaluate looting and other damage at over one thousand heritage sites in Egypt. Assessing imagery dating between 2002 and 2013, their results indicated an increase in visible damage to sites during this period caused by looting and encroachment, which by Parcak et al.’s definition “includes building development, cemetery growth, agricultural expansion and intentional damage through targeted destruction” (2016: 190). Their findings support the work of previous authors who have documented an increase in looting and other damage to archaeological sites connected with increasing nationwide economic and political instability (e.g. Ikram 2013; Ikram & Hanna 2013).